A SYSTEMATIC LITERATURE REVIEW ON THE DEVELOPMENT OF PEDAGOGICAL COMPETENCIES AMONG ISLAMIC RELIGIOUS EDUCATION TEACHERS IN THE DIGITAL AGE - Dadang Dadang; Arivan Mahendra; Jumhur Jumhur; Syarip Syarip (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
The rapid advancement of information technology in the 21st century has significantly transformed education, including Islamic Religious Education (PAI). In this digital era, teachers are required to adapt to increasingly open access to information and dynamic learning environments. This condition demands adaptive and innovative pedagogical competencies, enabling teachers to integrate digital technology effectively while maintaining Islamic values. This study aims to examine the challenges and opportunities in strengthening PAI materials in the digital age, focusing on curriculum transformation, pedagogical innovation, technology integration, and teachers’ digital competencies. Despite growing research on digital education, a gap remains in understanding how PAI teachers can holistically integrate digital pedagogy while preserving Islamic values a gap this review specifically addresses. This study uses a systematic literature review approach based on the PRISMA framework. Relevant studies published between 2015 and 2025 were collected from Google Scholar, Scopus, and ERIC. The selection process applied clear inclusion and exclusion criteria to ensure the quality and relevance of the studies. Data were analyzed thematically to identify key patterns and trends in developing pedagogical competencies in digital-based Islamic education. The findings indicate that pedagogical competence development is influenced by flexible curriculum design, innovative teaching approaches, technology integration, and the reinforcement of Islamic values. A key trend identified is the increasing adoption of AI-based personalized learning, while a critical gap remains in empirical evidence on the long-term outcomes of technology integration in Islamic education contexts. Approaches such as discovery learning, deep learning, and gamification enhance student engagement and understanding. Digital technologies, including artificial intelligence, enable personalized and more effective learning. However, challenges such as limited infrastructure, low digital literacy, and teachers’ readiness remain significant barriers, particularly in remote and under-resourced settings. In conclusion, strengthening PAI teachers’ pedagogical competencies requires a holistic approach that integrates curriculum flexibility, pedagogical innovation, and ethical use of technology aligned with Islamic values.